KAJIAN SIFAT FISIK DAN KIMIA TANAH PADA TANAH YANG DI TANAMI PADI GOGO (Oryza Sativa) DI DESA WAWONA KABUPATEN MINAHASA SELATAN - Maria Idie; Diane D. Pioh; Rafli I. Kawulusan (COCOS, 2017)
ABSTRACTThis study aims to determine the physical and chemical properties of soil on soil that plantedupland rice in Wawona Minahasa Selatan Village. This study was taken samples on soil that was plantedwith upland rice and land that is not planted in upland rice. This research was conducted by using surveymethod with composite sampling technique in Wawona Minahasa Tenggara Village at two locationsplanted and not planted with upland rice then under the soil sample to soil laboratory of Faculty ofAgriculture Unsrat for analysis of texture, permeability, soil pH, C -organic, N-total, K-available, andPhosphorus. This study found the physical properties of the soil texture of the soil in the village ofWawona at the location of the planted and not planted with gogo rice has the same texture class clayberliat. The permeability of soil at the location of planted upland rice was 7.48 cm / h - 8.98 cm / h whilein the unopested areas 7.23 cm / h-7.73 cm / hr. The soil chemistry properties are: soil pH at planted siteand not planted with upland rice pH value 6,78-6,80 with neutral criterion, C-organic at planted locationand not planted with upland rice have the same criterion that is being (2 , 08% -2.39%), soil nitrogen inthe planted site has low criterion (0.16% -0.17%) and at the unfertilized site has medium criterion (0.22%-0.24%) . Potassium in the planted and unlogged areas of upland rice has the same criteria that is verylow where in the cultivated tilapia criteria (0.068 me / 100g-0.076 me / g) and the unplanted location hasthe criterion (0.078 m / 100g-0.083 M / g).(15,46%) and in non-cultivated land have low criterion (11,56Ppm-12.81 ppm).Keywords of physical and chemical properties.